Application of Bacillus sp Liquid Formula Using Root Infusion Technique To Control VSD (Vascular Streak Dieback) Disease In Cocoa - Asrul Asrul; Kurnia Burhan; Irwan Lakani; Mutmainah Mutmainah; Umrah Umrah (Postgraduate, University of Mataram, 2024)
This study aims to explore the potential of liquid organic waste formula made from Bacillus sp to suppress the severity of vascular streak dieback (VSD) disease in cocoa plants. The research was conducted on smallholder cocoa plantations in Patimbe Village, Palolo Subdistrict, Sigi Regency, Central Sulawesi. The research was arranged in a non-factorial Randomised Group Design (RAK) with 5 treatments and 5 replications. The treatments consisted of control (P0=no formula); coconut water + Bacillus sp (P1); rice washing water + Bacillus sp (P2); tofu water + Bacillus sp (P3); and a combination of coconut water, rice washing water, and tofu water + Bacillus sp (P4). Each experimental unit consisted of 10 cocoa plants infected with VSD disease. The liquid organic waste formula was applied using the root infusion technique in months 1 and 3 at a dose of 250 ml/root. Observations of disease symptoms, disease development, disease severity, and disease suppression efficacy were conducted monthly. The results showed that the combination of organic waste of coconut water, tofu water, and rice washing water with Bacillus sp active ingredient was more effective in suppressing VSD disease than liquid organic waste alone with an effectiveness rate of 81.7%.